Peran Mediasi Strategi Coping dalam Hubungan antara Stres dengan Kinerja Akademik Mahasiswa Kelas Karyawan - Ningsih, Tasya Aprilia; Musnaini, Musnaini; Khouroh, Umu (Business Management Research, 2024)
This research is exploratory in nature and aims to explore the relationship between stress, coping strategies, and academic performance among working-class students. The research adopted a survey questionnaire design. Data on the causes of stress among working-class students and its impact on their academic performance were collected using a questionnaire. The research sample was working-class students. In total, 50 complete and valid questionnaires were obtained for further analysis. The data were analyzed using SEM-PLS. The results show that stress does not impact performance, but the coping strategies used can mediate this impact. The conceptual model developed in this research can provide a basis for how to address stress in order to improve academic performance and understand how the academic environment should be designed to address these issues.